1985
DOI: 10.1203/00006450-198508000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Adrenergic Control of Glycogenolysis in Rat Liver: The Significance of Changes in Receptor Density

Abstract: 25. Raul F, Noriega R, Ngi-Emvo E, Doffoel M, Grenier JF 1983 Lactase activity is under hormonal control in the intestine of adult rat. ABSTRACT. The present study examined the developAbbreviations mental changes in the adrenergic control of glycogenolysis in the rat model. A relatively new P-adrenergic radioligand, '251-iodocyanopindolol (ICP), was examined in binding assays with rat liver plasma membrane (LPM). I C P demonstrated both a higher specificity and a greater affinity for P-adrenergic receptors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…It is well known that the beta-adrenergic receptor stimulates intracellular CAMP formation by G-protein-mediated activation of adenylate cyclase. There are several reports that beta-receptor density and adenylate cyclase activity increase in liver during aging (Bendeck and Noguchi, 1985;Graham et al, 1987;Katz et al, 1987). Recently, several reports have also suggested that G-protein couplinghncoupling to betaadrenergic receptors is impaired during aging and disease (Anwar et al, 1991;Feldman et al, 1984;Montarnat and Davies, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the beta-adrenergic receptor stimulates intracellular CAMP formation by G-protein-mediated activation of adenylate cyclase. There are several reports that beta-receptor density and adenylate cyclase activity increase in liver during aging (Bendeck and Noguchi, 1985;Graham et al, 1987;Katz et al, 1987). Recently, several reports have also suggested that G-protein couplinghncoupling to betaadrenergic receptors is impaired during aging and disease (Anwar et al, 1991;Feldman et al, 1984;Montarnat and Davies, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The calculated density of the low-affinity binding site is in the same range as the number of copies in each hepatocyte found for other receptors involved in metabolic regulation, e.g. the a,-receptor with about 500 fmol/mg membrane protein [47,43], or the insulin receptor for which receptor numbers of 10000 copies/cell in binding studies [39,40] or 100000 copies/cell in morphometric studies [38] have been reported.…”
Section: Pg Receptor On Plasma Membranes Of Purified Hepatocytesmentioning
confidence: 89%
“…It should be noted that for the adrenergic agonists clear-cut differences in sensitivity and effectiveness have been reported between young and adult rats [1,2], male and female rats [3], and between different animal species: dog [4] and rabbit [5] hepatocytes display a greater sensitivity to ,-adrenergic agonists than do rat hepatocytes, whereas the liver of rabbit and guinea pig has more ,?than a-receptors [6]. Finally, a complete lack of vasopressin receptors has been reported in the liver of ob/ob mice as compared with their lean controls [7].…”
Section: Introductionmentioning
confidence: 99%